2008
DOI: 10.1111/j.1467-8276.2008.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Income Growth in Metropolitan and Nonmetropolitan Labor Markets

Abstract: This article analyzes determinants of growth across labor markets in the United States, using a production function approach based on four inputs: labor, manufacturing investment, human capital investment, and public capital investment. We find little role for public capital investment in growth, but that manufacturing investment spurred growth in nonmetropolitan areas, in contrast to metropolitan areas. We also find that human capital investment mattered more for metropolitan areas than for nonmetropolitan ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 35 publications
1
29
0
1
Order By: Relevance
“…We find a positive and significant correlation between initial educational attainment and income growth for both metropolitan and nonmetropolitan counties, similar to Hammond and Thompson (2008) and Higgins et al (2006). For nonmetropolitan counties, we find a positive and significant correlation for the unemployment rate for population and employment growth, which suggests that nonmetropolitan counties with greater labor market slack tend to grow faster.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…We find a positive and significant correlation between initial educational attainment and income growth for both metropolitan and nonmetropolitan counties, similar to Hammond and Thompson (2008) and Higgins et al (2006). For nonmetropolitan counties, we find a positive and significant correlation for the unemployment rate for population and employment growth, which suggests that nonmetropolitan counties with greater labor market slack tend to grow faster.…”
Section: Resultssupporting
confidence: 60%
“…This is also important in order to avoid possible selection bias in the results and resulting policy implications. As Hammond and Thompson (2008) and Higgins et al (2006) have shown, the impact of growth determinants differs significantly across metropolitan and nonmetropolitan regions. Further, nonmetropolitan counties accounted for a significant share of the U.S. population in 2004 (at 16.9 percent, or 49.7 million residents, using the 1999 MSA designations from the federal Office of Management and Budget).…”
Section: Empirical Methods and Datamentioning
confidence: 92%
“…Harden and Hoyt () found their results to be sensitive to the omission of small states on the border with Canada. Hammond and Thompson () found differences between metropolitan and nonmetropolitan areas. Peltzman () assessed the sensitivity of border county results to county size and type of state boundary, finding modest quantitative differences.…”
Section: Recent Trends In the Literaturementioning
confidence: 99%
“…Exceptions of studies using external instruments include Brown et al . (), Agostini (), Hammond and Thompson (), and Yu and Rickman (). Agostini () used dummy variables for statutory and constitutional budget limits as instruments.…”
Section: Recent Trends In the Literaturementioning
confidence: 99%
“…(2007) found that increased local tax burdens had a negative impact on income growth in Midwest rural counties, as did state personal and corporate income taxes. Hammond and Thompson (2008) found that human capital investment increased per capita income growth in US non‐metropolitan labour market areas, while public infrastructure investment did not. Huang et al.…”
Section: Introductionmentioning
confidence: 99%